2004
DOI: 10.1016/j.bone.2003.11.022
|View full text |Cite
|
Sign up to set email alerts
|

Delineating bone's interstitial fluid pathway in vivo

Abstract: Although interstitial fluid flow has been suggested to play a role in bone adaptation and metabolism, the constituents and ultrastructure of this interstitial fluid pathway are not well understood. Bone's lacunar-canalicular porosity is generally believed to be a continuous interstitial fluid pathway through which osteocytes sense external mechanical loading as well as obtain nutrients and dispose of wastes. Recent electron microscopy studies have suggested that a fiber matrix surrounds the osteocytic cell pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
107
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 118 publications
(109 citation statements)
references
References 28 publications
2
107
0
Order By: Relevance
“…Two key features of osteocytes as mechanosensors are their ability to detect mechanical stimuli and to send signals to other effector cells that regulate bone formation and resorption (5,6,56,58,59). Dynamic fluid flow is one of the mechanical stimuli that osteocytes experience in vivo with habitual loading (24,25,54). Previous studies have established that this loading-induced dynamic fluid flow is a potent physical signal in the regulation of bone cell metabolism (7,16,37,57), yet it is unclear what role it might play in osteocyte mediated regulation of bone resorption.…”
Section: Introductionmentioning
confidence: 99%
“…Two key features of osteocytes as mechanosensors are their ability to detect mechanical stimuli and to send signals to other effector cells that regulate bone formation and resorption (5,6,56,58,59). Dynamic fluid flow is one of the mechanical stimuli that osteocytes experience in vivo with habitual loading (24,25,54). Previous studies have established that this loading-induced dynamic fluid flow is a potent physical signal in the regulation of bone cell metabolism (7,16,37,57), yet it is unclear what role it might play in osteocyte mediated regulation of bone resorption.…”
Section: Introductionmentioning
confidence: 99%
“…The left jugular vein was then exposed surgically and a 25G5/8 needle attached to a 3-ml syringe was inserted into the vein to inject a bolus of tracer solution. Our previous experiments showed that ferritin was best detected if injected at a dosage of at least 150 mg/100 g of body weight [24]. We concentrated the ferritin solution using Amicon Ultra-4 centrifugal filter devices (100,000 molecular weight cutoff, Millipore, Billerica, MA), from 85 mg/ ml to a final solution of 309 mg/ml.…”
Section: Methodsmentioning
confidence: 99%
“…Our previous tracer studies indicate that ferritin injected into rats is confined to the bone blood vessels and does not pass into the mineralized matrix [24]. However, other investigators have shown that ferritin forms halo-shaped labeling that appears to enter the mineralized matrix around blood vessels, along with appositional fronts along the bone surfaces [5,15,16,19].…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations